Equality - Baker, J. author. aut Link
IX, 323 p.
Keywords: How can egalitarian ideals be put into action? This ground-breaking book sets out a new interdisciplinary model for equality studies. Integrating normative questions about the ideal of equality with empirical issues about the nature of inequality, it applies a new framework to a wide range of contemporary inequalities. Proposing far-reaching changes in the economy, politics, law, education and research practices, it sets out innovative political strategies for achieving those aims. It is an invaluable resource for both academics and activists.